Exploring the Incidence and Anatomical Distribution of Spermatic Cord Lipoma During Hernia Repair: A Ward-Based Study - Zahid Mehmood; Tanweer Ahmed; Maleha Salih; Sufyan Taufiq; Irfan Ali (Indus Journal of Bioscience Research, 2025)
Background: Spermatic cord lipomas, often overlooked during inguinal hernia repair, can mimic or accompany indirect hernias, potentially leading to postoperative complications if not identified and managed intraoperatively. This study aimed to evaluate the incidence and anatomical distribution of spermatic cord lipomas across different surgical modalities in a ward-based setting. Methods: A prospective observational study was conducted over 12 months (May 2024–April 2025) at Jinnah Postgraduate Medical Center, Karachi. A total of 140 male patients undergoing elective inguinal hernia repair were included. Surgical approaches comprised open repair (n=98), laparoscopic TAPP (n=22), and robotic TAPP (n=20). Intraoperative identification and localization of lipomas were recorded, categorized anatomically as precordial, midcordial, or proximal. Results: Spermatic cord lipomas were detected in 53 of 140 patients (37.9%). Incidence varied by surgical technique: robotic TAPP (50.0%), laparoscopic TAPP (45.5%), and open repair (33.7%). Midcordial location was most frequent (39.6%), followed by precordial (34.0%) and proximal (26.4%). Unilateral lipomas predominated (90.6%), while bilateral cases (9.4%) were exclusively identified via laparoscopic and robotic methods. No intraoperative complications related to lipoma dissection were reported. However, in cases where lipomas were missed or incompletely excised, postoperative complications such as recurrence, bulging, and persistent discomfort were noted during follow-up. Conclusion: Spermatic cord lipomas are a common intraoperative finding during inguinal hernia repair, especially in minimally invasive procedures where improved visualization enhances detection. Midcordial involvement is most prevalent, and bilateral cases may go unnoticed in open repairs. Standardized intraoperative evaluation of the spermatic cord is crucial to mitigate the risk of recurrence, postoperative bulging, and patient discomfort, thereby improving long-term outcomes.